Long-term outcomes after percutaneous withdrawal of HeartWare left ventricular assist device (HVAD) support: A 10-year update - Chokanan Thaitirarot; Leonard M. Shapiro; Clive Lewis; Jayan Parameshwar; Steven S.L. Tsui; Stephen J. Pettit (JHLT Open)
Ten years have passed since we reported percutaneous decommissioning of an implantable left ventricular assist device (LVAD) using 2 Amplatzer vascular plugs in a 17-year-old male who was bridged to recovery after 22 months of LVAD support. While his left ventricular (LV) dimensions never completely normalized and there has been persistent mild impairment of LV systolic function, the patient remains free of heart failure symptoms and his natriuretic peptide level has been well suppressed on guideline-directed medical therapy. He is anticoagulated with Warfarin. There have been no adverse events relating to either the decommissioned LVAD or the percutaneous driveline remnant, or anticoagulation. This case highlights the potential for long-term survival without adverse events in individuals who are left with a redundant implantable LVAD after successful percutaneous withdrawal of mechanical circulatory support.